The educational and sanitary concept of Juan Luis Vives: A Gadamerian-hermeneutic study - Juana María Hernández Conesa; Enrique Maldonado Suarez (Universidad de Alicante, 2014)
European fragmentation, due in part to the ratification of the Council of Trent, was a significant incident which allows a polyhedral analysis. From this moment, a new divergent and confronted way to rebuild the world was developed between "both Europes". This fact led to a two different mentalities preface from the braudelian perspective, co-existing under a continuous struggle. On one side, the North European Countries, which descended from the Protestant Reformation. On the other side were the South European Countries, inheriting the Counter-reformation proper and the Tridentine postulates. Our hypothetical proposal is derived from the educational and sanitary concept included in the work of Juan Luis Vives. Through its study it has been corroborated that, the European fragmentation had many consequences beyond the circumstantial time when it happened. In this research work, the source was studied following the hermeneutics analysis based on the Gadamerian interpretation.